The Effect of Using Origami Paper to Teach the Perimeter of Plane Figures on Cognitive Achievement of Students Grade IX - Yael Narwastu Jati; Dylmoon Hidayat (Polyglot, 2017)
This pre-experimental research design aims to know whether there is an effect of using origami paper to teach the perimeter of plane figures on cognitive achievement of students in grade IX and how the use of origami paper can affect students’ cognitive achievement. The subject was taken from 16 students of class IX-A as an experimental class that were going to study using origami paper as the teaching aid. The data obtained was students’ pre-test and post-test. The gained mean of students’ score between pre-test and post-test was significantly greater than the expected score 0.4, in fact the gain reached 0.82 which is categorized high. Thus, it can be concluded that there was an effect of using origami paper to teach the perimeter of plane figures on students’ cognitive achievement.BAHASA INDONESIA ABSTRAK: Desain penelitian eksperimen ini dilakukan untuk melihat apakah terdapat pengaruh penggunaan kertas origami untuk mengajar keliling dari suatu bidang datar terhadap hasil belajar kognitif siswa kelas IX dan bagaimana penggunaan tersebut mempengaruhi hsil belajar. Sampel penelitian adalah 16 siswa kelas IX-A sebagai kelompok ekperimen yang akan menggunakan kertas origami. Data diperolehh dari hasil pre-tests dan post-tests. Hasil penelitian menunjukkan ada perbedaan rata-rata skor yang signifikan antara hasil pre-tests dan post-tests yang di duga, yaitu 4.0 (normalized gain), bahkan mencapai 0.8 yang termasuk golongan tinggi. Sehingga, dapat disimpulkan bahwa terdapat pengaruh pada hasil belajar kognitif pada pengajaran keliling suatu bidang datar dengan menggunakan kertas origami